From war to peace. The contribution of military corps with police functions: the GNR in Iraq - Graça, Pedro Miguel Duarte da (2015)
The nature of conflict is changing. The occurrences of formal international intervention, in a complex theater of operations with operational requirements, necessitate the engagement of international forces with military and civilian capabilities, namely a distinctive type of police force. Since the end of the last century, the Portuguese Republican National Guard (GNR) has deployed to stabilize various conflicts throughout the world. The GNR contributed when UN resolutions mandated constabulary requirements, but this participation was never framed within a multinational force of NATO. However, the GNR works under the same NATO doctrine for force employment constituted on the basis of military units with police functions, called the Multinational Specialized Units. The Guard is a military organization with the expertise to contribute to peace. This unique competence stems from capabilities over the entire spectrum of police functions within unstable environments, including a unique ability to overcome the Security Gap. Likewise, by concurrently deploying with the military forces, the GNR demonstrates the ability to use force in a legal manner by fostering a comprehensive approach within the security and judiciary system. This holistic capacity goes beyond a purely institutional approach. By executing police functions in unstable environments the GNR contributes to the pursuit of credible Portuguese foreign policy interests in Peace-Enforcement Operations..